2016
DOI: 10.1038/nrurol.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for organ-confined prostate cancer: is less more?

Abstract: Moderate hypofractionation of radiotherapy is widely considered a viable alternative to conventional fractionation for the treatment of patients with organ-confined prostate cancer, but stereotactic body radiotherapy (SBRT) is rapidly emerging as a novel treatment modality for this disease. Advances in treatment planning, image guidance, target position reproducibility and on-line tracking, coupled with a compelling radiobiological rationale, have promoted SBRT as a safe and effective treatment. Dose escalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Current reimbursement policies in the US and many countries in Western Europe incentivize longer RT courses. [28][29][30][31] Practice changes that are viewed as "doing less" also may face greater resistance 32 ; however, shorter RT courses currently are under investigation for several malignancies 22,33,34 Interestingly, patterns-of-care studies have suggested that nonclinical factors such as insurance status and institutional characteristics are influential in the selection of RT fractionation regimens. 21,[23][24][25][26][27] Potential barriers to implementing new evidence-based practices include workplace culture, lack of training, knowledge gaps, limited skills in applying research findings to individual patient situations, unwillingness to change, patient preferences, administrative policies, and poor generalizability of study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current reimbursement policies in the US and many countries in Western Europe incentivize longer RT courses. [28][29][30][31] Practice changes that are viewed as "doing less" also may face greater resistance 32 ; however, shorter RT courses currently are under investigation for several malignancies 22,33,34 Interestingly, patterns-of-care studies have suggested that nonclinical factors such as insurance status and institutional characteristics are influential in the selection of RT fractionation regimens. 21,[23][24][25][26][27] Potential barriers to implementing new evidence-based practices include workplace culture, lack of training, knowledge gaps, limited skills in applying research findings to individual patient situations, unwillingness to change, patient preferences, administrative policies, and poor generalizability of study results.…”
Section: Discussionmentioning
confidence: 99%
“…21,[23][24][25][26][27] Potential barriers to implementing new evidence-based practices include workplace culture, lack of training, knowledge gaps, limited skills in applying research findings to individual patient situations, unwillingness to change, patient preferences, administrative policies, and poor generalizability of study results. [28][29][30][31] Practice changes that are viewed as "doing less" also may face greater resistance 32 ; however, shorter RT courses currently are under investigation for several malignancies 22,33,34 Interestingly, patterns-of-care studies have suggested that nonclinical factors such as insurance status and institutional characteristics are influential in the selection of RT fractionation regimens. 25,35,36 Approximately 20% of respondents in the current survey indicated that a capitated payment system would affect their selection of SC-RT versus LC-CRT for patients with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some like Baumann et al [98] suggest that with recent technological advances in radiotherapy, new research and developments should focus less on improving the dose distribution and more on reducing treatment times [99]. If the use of SRBs for radiation boosting or priming the abscopal effect can lead to hypofractionation, the anticipated benefit of reducing treatment times would resonate with this suggestion.…”
Section: Challenges and Opportunities For Future Research And Devementioning
confidence: 99%
“…Additionally, we did not evaluate the impact of NTDR among hypofractionated schedules, which are increasingly used among prostate cancer patients . Extremely hypofractionated schedules may have mechanisms for cellular death similar to brachytherapy, and it is unclear if treatment breaks of days would have significant impact on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%